Evaluating Invasive Marbled Crayfish as a Potential Livestock for Sustainable Aquaculture - Tönges, Sina; Masagounder, Karthik; Lenich, Frank; Gutekunst, Julian; Tönges, Marvin; Lohbeck, Jasmin; Miller, Aubry K.; Böhl, Florian; Lyko, Frank (Frontiers in Ecology and Evolution, 2021)
The marbled crayfish (Procambarus virginalis) is a recently discovered freshwater crayfish species, which reproduces by apomictic parthenogenesis, resulting in a monoclonal, all-female population. The animals were widely distributed through the aquarium trade and have established numerous stable wild populations through anthropogenic releases. They are highly prevalent in Madagascar, where they have become a popular source of nutritional protein. As freshwater crayfish aquaculture in open systems is a thriving, but ecologically damaging global industry, alternatives are urgently needed. Although marbled crayfish are often branded by their invasive mode of reproduction, their overall invasiveness is not higher than for other cultured crayfish species. Furthermore, their resiliency and high adaptability provide a strong rationale for evaluating them for closed and environmentally safe aquaculture approaches. Here we describe a novel population of marbled crayfish in a former German coal mining area that is characterized by acid and polluted water. Even under these adverse conditions, animals grew to sizes and weights that are comparable to commercially farmed freshwater crayfish. Tailored feed development and laboratory testing demonstrated highly efficient feed conversion, suggesting a considerable capacity for sustainable production in closed systems. We further show that marbled crayfish meat can be readily introduced into European meals. Finally, chemical analysis of marbled crayfish exoskeletons revealed comparably high amounts of chitin, which is a valuable source for the synthesis of chitosan and bioplastics. Our results thus suggest that production of marbled crayfish in closed systems may represent a substantially more sustainable alternative for crayfish aquaculture.